Examining the mediating role of green purchasing practices in the relationship between environmental knowledge and procurement sustainability - ALIMATU SADIA SUMAILA (KNUST, 2024)
A Thesis submitted to the Department of Supply Chain and Information Systems, School of Business in partial fulfillment of the requirements for the degree of Master of science in procurement and supply chain management